18F-Fluorodeoxyglucose positron emission tomography-computed tomography imaging in HIV-infected patients with lymphadenopathy, with or without fever and/or splenomegaly. (June 2018) - Jain, L; Mackenzie, S; Bomanji, JB; Shortman, R; Noursadeghi, M; Edwards, SG; Miller, RF
We audited whether 18 F-Fluorodeoxyglucose positron emission tomography-computed tomography ( 18 FDG PET-CT) imaging could discriminate between different diagnoses in HIV-infected patients presenting with lymphadenopathy, with or without fever and/or splenomegaly. Maximum standardised uptake (SUVmax ) values were similar in lymphoma and mycobacterial and fungal infections and were lower but similar in those with human herpesvirus (HHV) 8-associated disease and HIV-associated reactive lymphadenopathy. Nodal 18 FDG avidity, with SUVmax ≥10, excluded diagnoses of HHV 8-associated disease and miscellaneous conditions, and HIV-associated reactive lymphadenopathy was additionally excluded in those who had undetectable plasma HIV viral loads. This audit suggests 18 FDG PET-CT imaging did not permit discrimination between specific diagnoses but has utility in identifying lymph nodes with increased avidity that could be targeted for biopsy and in ruling out significant pathology.